2017
DOI: 10.1093/protein/gzx039
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of residues around the active site tunnel towards generating a glucose-tolerant β-glucosidase from Agrobacterium tumefaciens 5A

Abstract: Most β-glucosidases are subjected to inhibition by the final hydrolysis product glucose resulting in the accumulation of cellobiose and oligosaccharides. This accumulated cellobiose and oligosaccharides further inhibit the activities of endoglucanase and cellobiohydrolases, resulting in the inhibition of cellulose degradation and a more expensive biofuel. To elucidate the mechanism(s) of glucose tolerance, we designed and characterised six mutations of a moderately glucose-tolerant β-glucosidase (H0HC94) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…Whereas the typical inhibition constant ( K i,app ) of glucose on the β-glucosidase chromogenic substrate, p -nitrophenyl-β- d -glucoside ( p NPGlc), is less than 50 mM, recently there have been reports of bacterial β-glucosidase that are either not inhibited by glucose or are stimulated in the presence of glucose. 6,8,9 Thus, there exists a large difference in glucose inhibition amongst β-glucosidase. Though the molecular mechanism of glucose inhibition or tolerance is not well understood, experimental studies of glucose-tolerant β-glucosidase have attributed tolerance to narrower and deeper active site tunnels, specific residues in the tunnel, and the presence of allosteric sites on these enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the typical inhibition constant ( K i,app ) of glucose on the β-glucosidase chromogenic substrate, p -nitrophenyl-β- d -glucoside ( p NPGlc), is less than 50 mM, recently there have been reports of bacterial β-glucosidase that are either not inhibited by glucose or are stimulated in the presence of glucose. 6,8,9 Thus, there exists a large difference in glucose inhibition amongst β-glucosidase. Though the molecular mechanism of glucose inhibition or tolerance is not well understood, experimental studies of glucose-tolerant β-glucosidase have attributed tolerance to narrower and deeper active site tunnels, specific residues in the tunnel, and the presence of allosteric sites on these enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a program to understand how the β-glucosidase reaction product, glucose, interacts with the enzyme, we have been studying the effects of glucose on β-glucosidase across mesophilic and thermophilic organisms. 6,9,24 One such enzyme is the highly active and thermostable GH1 β-glucosidase (B8CYA8) from Halothermothrix orenii . 24,25 The higher stability of this enzyme has been shown to be a promising target toward industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…In another investigation, the introduction of additional disulfide bridges in the catalytic module of Talaromyces emersonii Cel7A resulted in mutants (G4C/A70C, N54C/P191C and T243C/A375C) with improved thermostability ( Voutilainen et al, 2009 ). For the glucose tolerance of β-glucosidase, the structure between subsites +1 and +2 is critical ( Matsuzawa et al, 2016 ; Goswami et al, 2017 ).…”
Section: Factors Governing Thermostability and Kinetics Of Cellulasesmentioning
confidence: 99%
“…This study concluded that structure between subsites +1 and +2 might be important for the glucose tolerance and substrate specificity of Td2F2 ( Matsuzawa et al, 2016 ). The mutant β-glucosidase from Agrobacterium tumefaciens , with increased hydrophobicity at +1 subsite and hydrophobicity and steric at +2 subsite, displayed 2.2-fold higher tolerance to glucose ( Goswami et al, 2017 ).…”
Section: Engineering For Glucose Tolerant β-Glucosidasementioning
confidence: 99%
“…The capability of microbial cellulases to digest cellulose into glucose subunits could thus play a critical role in biomass conversion into renewable energy. Impediments include overcoming the recalcitrance of plant biomass; more specifically, our general lack of understanding of the interaction mechanisms between enzymes and biomass; how cellulases can direct individual strands of cellulose from a semicrystalline substrate into their active sites for catalysis (Goswami, Das, & Datta, ). The process by which different cellulases can interact synergistically to accelerate the degradation process is also unclear.…”
Section: Introductionmentioning
confidence: 99%